2020
DOI: 10.36740/wlek202005140
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Enterovirus-Associated Encephalitis in a Young Adult Coinfected With Borrelia Burgdorferi

Abstract: The aim: To pay attention of clinicians to sterile encephalitis in adults, which in fact may be caused by EVs. Results: A young woman was admitted to our clinic because of 3-month-history of mild fever, left-sided soft facial paralysis, and generalized weakness. MR brain imaging in T2W, FLAIR, and T1W mode showed focal hyper intensive abnormalities in various parts of the left hemisphere. EV RNA was detected in the patient’s CSF on admission. IgM class antibodies to B.burgdorferi were present in the blood. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[3] EBV DNA can exist outside the host chromosome or be incorporated into the host cell genome. [4] Second, EBV not only releases toxins directly into the nervous system through the immune-mediated effect of CD8 + T lymphocytes, but also produces antigen-antibody complexes that can cause brain cell damage. EBV is the causative agent of infectious mononucleosis and has also been linked to a variety of diseases, such as childhood lymphoma and nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[3] EBV DNA can exist outside the host chromosome or be incorporated into the host cell genome. [4] Second, EBV not only releases toxins directly into the nervous system through the immune-mediated effect of CD8 + T lymphocytes, but also produces antigen-antibody complexes that can cause brain cell damage. EBV is the causative agent of infectious mononucleosis and has also been linked to a variety of diseases, such as childhood lymphoma and nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…2). Dyachenko et al 19 reported that 48 (21.2%) of 226 patients with acute encephalitis had evidence of EBV infection, including 24 (50%) with EBV monoinfection. CSF cytosis, protein and glucose content of these patients were close to normal, and MRI showed nonspecific focal (58.3%) and diffuse (31.3%) changes in the brain parenchymal.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis is generally good in the pediatric clientele and disabling sequela are uncommon. 54,55 The diagnosis is based on EBV DNA in cerebrospinal fluid (CSF) and serum by PCR. The CSF of patients with EBV meningitis/encephalitis typically shows pleocytosis, slightly increased protein levels, and atypical lymphocytes.…”
Section: Neurologic Disorders Associated With Lytic Ebv Infection Ebv...mentioning
confidence: 99%
“…However, the prognosis is generally good in the pediatric clientele and disabling sequela are uncommon. 54 , 55 …”
Section: Ebv-mediated Cns Pathologymentioning
confidence: 99%